FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TENAGA PENJUAL Studi Kasuspada Sales Promotion GirlPTXYZ Wilayah Jakarta - , Ignatius Teddy S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research are to find factors that can improve the perfomance of salesperson (Sales Promotion Girl) at PT. XYZ of Jakarta area. Salesperson performance can be obtained if the salesperson is doing a real effort in work tasks, especially in achieving sales targets. Therefore, this research uses several variables that affect the sales force effort to improve its performance , there is self efficacy, job satisfaction, positive feedback and negative feedback. This research uses several variables are taken from previous research that have been developed, there is the research from Sujan et al. (1994), Brown and Peterson (1994), Srivastava et al. (2001), Khrisnan et al. (2002), and Jaramillo et al. (2008). Population and sample throughout the research is a salesperson PT XYZ Jakarta area with a number of 103 people. Analysis technique used is Structural Equation Modeling or SEM is operated through the program AMOS version 19. The results showed higher self-efficacy, job satisfaction, positive feedback and negative feedback, is the greater the salesperson's efforts that resulted in the higher performance of salesperson.